MONITORING THE FORMATION OF UNIVERSAL COMPETENCES OF STUDENTS - Medvedeva, Irina; Martynyuk, Oxana; Pankova, Svetlana; Solovyova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Monitoring the quality of students’ mastering educational programs is an important component of the educational process. Monitoring achieved learning outcomes is the collection, processing and analysis of competence level data in order to make management decisions in the field of education quality. Currently in Russia there are not enough scientifically based methods for assessing and monitoring students' competences.The staff of the Laboratory of quality problems in higher education at Pskov State University has been conducting research in the field of assessment and monitoring students' competences, including universal ones, for more than ten years. The assessment center, the students' self-assessment, the students' portfolio evaluation, the expert assessment during Internship and during the final exams are held on different courses of study.The purpose of this article is to analyze the experience of monitoring the formation of universal students’ competences of the Faculty of Physics and Mathematics of Pskov State University during the entire period of study. The article contains a model of monitoring universal students’ competences.The research used the following methods: analysis of the scientific literature, assessment center, questioning, observation, expert evaluation.